Intraband transitions in dimerized semiconductor superlattices - Arrieta, D. I. (2011)
In some devices, the functionning of them is based in the interband transitions in which the electrons and holes recombine emitting photons in the visible and infrared regions. In a superlattice is formed several minibands separated by minigaps, between them may be induced intraband transitions that emitting photons in the infrarred and microwaves regions. In the present work, we develop a model that permit us calculate the probabilities per unit time of such transitions and that permit us identify the transitions used in a quantum cascade laser. We simulate two superlattice type, one with a 100 Å quantum well and the second with two dimerized quantum wells of 100 and 150 Å. In the first case, we clearly identify three cascade transitions and, in the second, we do not observe the possibility of a quantum cascade transition. But, we find a possible evidence of the competition of entanglement states belonging to 100 and 150 Å quantum wells.